Chromium Enrichment on P11 Ferritic Steel by Pack Cementation - F. A., Fauzi; Kurniawan, Tedi; Y. S., Bin; W. S., Wan Harun (EDP Sciences, 2016)
The future thermal power plant is expected to operate at higher temperature to improve its efficiency and to reduce greenhouse gas emission. This target requires better corrosion properties of ferritic steels, which commonly used as materials for superheater and reheater of boiler tubes. In this work, chromium enrichment on the surface of ferritic steel is studied. The deposited chromium is expected to become a reservoir for the formation of chromia protective layer. Chromium was deposited on the substrate of steel by pack cementation process for two hours at the temperature of 850ºC, 950ºC and 1050ºC, respectively. XRD analysis indicated that chromium was successfully deposited at all temperatures. Somehow, SEM cross sectional image showed that continuous layer of chromium was not continuously formed at 850oC. Therefore, this research clarify that chromium enrichment by pack cementation may be conducted at the temperature above 950oC